Peripheral Sensory Organs Contribute to Temperature Synchronization of the Circadian Clock in Drosophila melanogaster - George, Rebekah; Stanewsky, Ralf (Frontiers in Physiology, 2021)
Circadian clocks are cell-autonomous endogenous oscillators, generated and maintained by self-sustained 24 hou r rhythms of clock gene expression. In the fruit fly Drosophila melanogaster, these daily rhythms of gene expression regulate the activity of approximately 150 clock neurons in the fly brain, which are responsible for driving the daily rest/activity cycles of these insects. Despite their endogenous character, circadian clocks communicate with the environment in order to synchronize their self-sustained molecular oscillations and neuronal activity rhythms (internal time) with the daily changes of light and temperature dictated by the Earth’s rotation around its axis (external time). Light and temperature changes are reliable time cues (Zeitgeber) used by many organisms to synchronize their circadian clock to the external time. In Drosophila, both light and temperature fluctuations robustly synchronize the circadian clock in the absence of the other Zeitgeber. The complex mechanisms for synchronization to the daily light-dark cycles are understood with impressive detail. In contrast, our knowledge about how the daily temperature fluctuations synchronize the fly clock are rather limited. Whereas light synchronization relies on peripheral and clock-cell autonomous photoreceptors, temperature input to the clock appears to rely mainly on sensory cells located in the peripheral nervous system of the fly. Recent studies suggest that sensory structures located in body and head appendages are able to detect temperature fluctuations and to signal this information to the brain clock. This review will summarize these studies and their implications about the mechanisms underlying temperature synchronization.